Inferring denudation variations from the sediment record; an example of the last glacial cycle record of the Golo Basin and watershed, East Corsica, western Mediterranean sea. (3rd July 2012) - Calvès, G.; Toucanne, S.; Jouet, G.; Charrier, S.; Thereau, E.; Etoubleau, J.; Marsset, T.; Droz, L.; Bez, M.; Abreu, V.; Jorry, S.; Mulder, T.; et al.
Abstract Geophysical data and sampling of the Golo Basin (East Corsica margin) provide the opportunity to study mass balance in a single drainage system over the last 130 kyr, by comparing deposited sediments in the sink and the maximum eroded volume in the source using total denudation proxies. Evaluation of the solid sediments deposited offshore and careful integration of uncertainties from the age model and physical properties allow us to constrain three periods of sedimentation during the last climatic cycle. The peak of sedimentation initiated during Marine Isotopic Stage (MIS) 3 (ca. 45 ka) and lasted until late in MIS 2 (ca. 18 ka). This correlates with Mediterranean Sea palaeoclimatic records and the glaciation in high altitude Corsica. The yield of solid sediment into the Golo Basin drops in the observed present day Mediterranean basins (gauging stations), whereas the palaeo‐denudation estimate derived from the sediments over the last glacial period is one to ten times higher than that predicted using cosmogenic or thermochronometer estimates of exhumation. The catchment‐wide denudation rate calculated from deposited solid sediment ranges from 47 to 219 mm kyr−1, which is higher than the estimate from palaeosurface ablation in the proximal part of the source (9–140 mm kyr−1) and lower than the distal, narrow, incised channel of the Golo River (160–475 mm kyr−1). This mismatch raises questions about the investigation of denudation at millennial‐time scale (kyr) and at higher integrating times (Myr) as a reliable tool for determining the effect of climate change on mountain building and on sedimentary basin models.